Drivkræfter og barrierer i offentlige-private partnerskaber (OPP): En procesevaluering af det første kommunale OPP-projekt om erhvervsudvikling, vækst og arbejdspladser - Brogaard, Lena; Petersen, Ole Helby (Politik, 2015)
This article presents the results of a process evaluation of the rst public-private partnership (PPP) in a Dan- ish municipality established with the aim of creating economic growth and new jobs among local businesses. e article focuses on drivers and barriers and builds on program evaluation theory. e analysis shows that the intention of a partnership-based collaboration between the municipality and private business has only partially been achieved. Di culties with realizing the expected bene ts were especially due to unclear decision-procedures and changing objectives by the public partner in the PPP project.